Continuity in the parameter for the solutions of one-dimensional boundary-value problems for differential equations of higher orders in Slobodetsky spaces - Maslyuk, H. O.; Mikhailets, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We introduce the most general class of linear boundary-value problems for systems of ordinary differential equations of order r ≥ 2 whose solutions belong to the Slobodetsky space ^Ws+r_p( (a, b),C_m), where m N, s > 0 and p (1,∞ ). We also establish sufficient conditions under which the solutions of these problems are continuous functions of the parameter in the Slobodetsky space W^s+r_p( (a, b),C_m).